The language learning benefits of extensive reading: teachers should be good role models. - Krishnan, Gopala; Abdul Rahim, Rozlan; Marimuthu, Rasaya; Abdullah, Rahman; Mohamad, Faizah; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
Visioning a world class university is certainly an appropriate target for a university. Realizing this vision would need an expansion of knowledge and greater English proficiency as in this period of history, English is the language of IT which is an important key to acquiring knowledge. Using a sample of 40 level one students from UiTM Dungun this study found that in tandem with studies done elsewhere, extensive reading does seem to make a difference in the proficiency level of the students. Further the study also found that students who have a positive predisposition towards English read more and achieved better grades. However the study found no difference in the amount of reading done by boys and girls. The study discussed qualitatively the ability of teachers to inculcate the reading interest in the students, thus it is a triangular study which employs quantitative and qualitative means.